A Scientometric Analysis on Halal Awareness - Nadia Nurul Izza (Halal Tourism and Pilgrimage, 2022)
This study aims to determine the development and trend of halal awareness maps published by Scopus indexed journals. The data analyzed were 200 publications of published documents. The export data is then processed and analyzed using the R Bibliometrix application program combined with VOSviewer to determine the halal awareness bibliometric map for research development. The results showed that the number of publications with the theme of halal awareness experienced a significant increase. The results showed that the most popular journal was the Journal of Islamic Marketing, the most popular author was Abdullah A., and the most popular country was Malaysia. The most popular keyword topics are halal product, food industry, halal certification, halal logo and halal tourism. Furthermore, in conceptual structure, this research has spread thematic maps to place themes and sub-themes on the graph and divided them into four clusters (dropping or emerging themes, basic themes, highly developed and isolated themes, motor themes). Then, the conceptual framework developed will provide the necessary incentives for continued research in this emerging topic, which will benefit academics, researchers and practitioners around the world.